النظام القانوني للمصنفات الرقمية في التشريع - نسيمة ثلايجية; خولة حمروني (My University, 2022)
summary: The emergence and evolution of the technological revolution has led to the spread of digital classifications very rapidly Legislation has accelerated its protection, including the Jazarri legislature, in order to keep pace with these developments, on the one hand, and on the other hand to provide legal protection and the protection of new classifications, namely software, Databases, multimedia classifications organized by Ordinance 03-05 on copyright and adjacent rights, This is in order to address all violations and attacks, whether piracy or tradition's circumvention. ............................ الملخص العام : لقد أدى ظهور وتطور الثورة التكنولوجية إلى إنتشار المصنفات الرقمية بسرعة كبيرة، حيث سارعت التشريعات في حمايتها ومن بينها المشرع الجازئري كغيره لمواكبة هذه التطوارت من جهة ومن جهة أخرى إضفاء الحماية القانونية عليها وحماية المصنفات الجديدة والتي تتمثل في برامج الحاسوب، قواعد البيانات، مصنفات متعددة الوسائط نظمها بموجب الأمر 03-05 المتعلق بحقوق المؤلف والحقوق المجاورة، وذلك من أجل التصدي لكل الإنتهاكات والإعتداءات سواء كانت القرصنة أو طرق التحايل المتمثلة في التقليد. ...................... Résumé général : L’émergence et l’évolution de la révolution technologique ont conduit à la diffusion très rapide des classifications numériques La législation a accéléré sa protection, y compris la législature Jazarri, afin de suivre le rythme de ces développements, d’une part, et d’autre part pour assurer la protection juridique et la protection des nouvelles classifications, à savoir les logiciels, les bases de données, les classifications multimédias organisées par l’ordonnance 03-05 sur le droit d’auteur et les droits voisins, afin de traiter toutes les violations et les attaques, le piratage ou le contournement de la tradition.